1955
DOI: 10.1172/jci103225
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of the Sweat Glands

Abstract: The rate of sweat secretion has been shown to decrease during prolonged exposure to heat (1-3). This phenomenon has practical importance in the etiology of heat stroke, since the evaporation of sweat is the only significant means for dissipating heat when the environmental temperature equals or exceeds the body temperature.It is not known whether this decrease in sweating rate is due to a failure of the sudomotor center or to an exhaustion of the peripheral glandular units. The present, investigation was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1957
1957
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…Similar patterns of evaporative loss have been found in some wild East African bovids (Robertshaw & Taylor, 1969). A prominent feature of sweating in sheep and goats is the rapid decline in the amount of sweat produced at each discharge, an apparent 'fatigue' (Robertshaw, 1968 gland function has been noted in man after prolonged exposure to hot humid conditions and also after repeated administration of acetyl-/5-methylcholine (Thaysen & Schwartz, 1955; Collins, Sargent & Weiner, 1959). It can also be produced in a localized area of skin by preventing the evaporation of sweat and it has been suggested that sweat gland 'fatigue' in man is caused by hydration of the skin and obstruction of the sweat gland ducts.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar patterns of evaporative loss have been found in some wild East African bovids (Robertshaw & Taylor, 1969). A prominent feature of sweating in sheep and goats is the rapid decline in the amount of sweat produced at each discharge, an apparent 'fatigue' (Robertshaw, 1968 gland function has been noted in man after prolonged exposure to hot humid conditions and also after repeated administration of acetyl-/5-methylcholine (Thaysen & Schwartz, 1955; Collins, Sargent & Weiner, 1959). It can also be produced in a localized area of skin by preventing the evaporation of sweat and it has been suggested that sweat gland 'fatigue' in man is caused by hydration of the skin and obstruction of the sweat gland ducts.…”
Section: Introductionsupporting
confidence: 61%
“…The 'fatigue' of sweat gland activity induced in man by exposure to severe heat is similar in nature, i.e. the number of active glands does not diminish (Thaysen & Schwartz 1955).…”
Section: Discussionmentioning
confidence: 99%
“…Eccrine sweat glands exhibit a relatively high resistance to failure during continuous stimulation by low concentrations of acetylcholine (ACh), although high concentrations rapidly desensitize the glands (Collins, Sargent & Weiner, 1959). After 6 hr of thermal sweating the response to methacholine is reported to decrease (Thaysen & Schwartz, 1955) and this has been taken as evidence for 'fatigue' of the sweat glands. In the present experiments on seven subjects in environments of 460 C dry bulb/30°C wet bulb or 400 C dry bulb/32°C wet bulb, it was found that the sweat response to ACh did not decrease significantly, that sweat rate decreased by less than 30 % of the initial maximum, and that skin and rectal temperatures increased steadily during 3-5 hr of heat exposure.…”
Section: Pmentioning
confidence: 99%
“…In an area of the skin repeatedly injected with 400 Kg ACh or methacholine without atropine there was little reaction to the test doses and a slow recovery from the depression took place during the following 12 hr. Thaysen & Schwartz (1955) suggest that the decrease in sweat gland activity by repeated injections of drugs is due to 'fatigue' of the glands. We have found, however, that the depression by drugs does not necessarily entail prolonged or intense secretory activity and that the NaCl concentration of the sweat does not increase as is the case in thermal sweat gland 'fatigue' (Robinson & Robinson, 1954).…”
Section: Pmentioning
confidence: 99%